Sixteen new orthoclads (Chironomidae: Diptera) and new faunistic records from a patch of cloud forest in Zurquí de Moravia, Costa Rica - Namayandeh, Armin (Zootaxa, 2026)
This study is part of the Zurquí All Diptera Biodiversity Inventory, an effort to estimate the richness of the megadiverse order Diptera from Costa Rica. In this study, 16 new Orthocladiinae (Chironomidae) species are described. Bryophaenocladius borkenti sp. nov., Bryophaenocladius browni sp. nov., Bryophaenocladius epleri sp. nov., Bryophaenocladius porrasae sp. nov., Bryophaenocladius ulateae sp. nov., and Bryophaenocladius zumbadoi sp. nov., are distinguished by a well-reduced anal point and gonostylus with a dorsobasal ridge. Colosmittia elviae sp. nov. has a gonostylus with a trifid mega seta. Ionthosmittia lepizae sp. nov., a new faunistic record for the Neotropics, is distinguished from its congeners by the contrasting coloration of its tergites, low antennal ratio, and shape of its anal point and inferior volsella. Metriocnemus hernandezae sp. nov. is characterised by a virga with three compacted spines surrounded by a hyaline lamella on both sides, a long gonostylus with a slightly expanded apex, and a developed crista dorsalis, stretching over the anterior 1/3rd of the gonostylus. Metriocnemus picadoae sp. nov. is characterised by an inferior volsella posteriorly located and expanded on the gonocoxite. Parametriocnemus avilae sp. nov., Parametriocnemus lizanoi sp. nov., Parametriocnemus moragai sp. nov., and Parametriocnemus viquesi sp. nov. are distinguished from their congeners by a low antennal ratio, eyes with squared dorsomedial extension, and the antennal ultimate flagellomere with numerous long, curved sensilla chaetica, and well-sclerotized aedeagal lobes. Pseudorthocladius (Pseudorthocladius) edrisghaderii sp. nov., a new faunistic record for the Neotropics, is characterized by a circular-shaped anal point with a wide and round apex, covering most of tergite IX, inferior volsella well-reduced and rounded, and gonostylus bearing a large preapical spine and smaller spines on the dorsal surface. Titimbera holdenae sp. nov. is uniquely placed in its genus, and it is distinguished by its gonostylus shape and acrostichals placement on the scutum. Its scalpellate acrostichals and extremely extended costa of the wing place it in Titimbera.